2021
DOI: 10.1136/rmdopen-2020-001396
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary team intervention to reduce the nocebo effect when switching from the originator infliximab to a biosimilar

Abstract: ObjectivesTo evaluate an intervention to reduce the nocebo effect (NE) when switching from the originator infliximab (OI) to the infliximab biosimilar SB2 in chronic inflammatory rheumatic disease (CIRD).MethodsAn intervention was built with healthcare professionals (HPs) and a patient representative, based on a systematic review of interventions reducing the NE in musculoskeletal diseases and semi-directed questioning of five patients. Our strategy consisted of training HPs, switch information given by the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 39 publications
(98 reference statements)
1
24
0
1
Order By: Relevance
“…Nevertheless, since we have been discussing this intensively in our team [21] we cannot exclude that the rheumatologist and the nurse who provided the information on bsDMARDs has taken advantage of positive framing. One smaller study indicated that possible nocebo effects may be reduced by a tailored communication with a prominent role of nurses [42]. Finally, not only switching but also not multiswitching seemed to be a major problem for patients with CIRD which is consistent with an early controlled study on multiswitching [43] and our data on the lack of nocebo effects in patients switched from originator to a biosimilar [44].…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, since we have been discussing this intensively in our team [21] we cannot exclude that the rheumatologist and the nurse who provided the information on bsDMARDs has taken advantage of positive framing. One smaller study indicated that possible nocebo effects may be reduced by a tailored communication with a prominent role of nurses [42]. Finally, not only switching but also not multiswitching seemed to be a major problem for patients with CIRD which is consistent with an early controlled study on multiswitching [43] and our data on the lack of nocebo effects in patients switched from originator to a biosimilar [44].…”
Section: Discussionsupporting
confidence: 89%
“…Almost one decade after the first approval of a monoclonal antibody biosimilar by the EMA in 2013 [43], an underestimated phenomenon has been observed in patients treated with biological drugs: the nocebo effect [44][45][46][47].…”
Section: Nocebo Effect In Ibdmentioning
confidence: 99%
“…More recently, Biosimilars in Inflammatory Bowel Diseases: General Concepts and Clinical Implications DOI: http://dx.doi.org/10.5772/intechopen.100452 after the beginning of the biosimilar era, the concept of nocebo was revisited and defined as the negative equivalent of the placebo effect. Since then, this concept has received considerable attention in both clinical research and clinical practice [44][45][46]. Even though medical evidence supports biosimilar use, several barriers were created to hinder more widespread adoption of these drugs into current medical practice.…”
Section: Nocebo Effect In Ibdmentioning
confidence: 99%
“…Fortunately, the nocebo effect has gained recent prominence in biosimilars therapy [ 29 , 30 ]. The importance of patient education to mitigating the effect has also been recognized [ 30 ] and researchers are beginning to be able to measure its impact [ 31 ]. Patient education should be a two-pronged strategy.…”
Section: Patient Education and The Nocebo Effectmentioning
confidence: 99%
“…The key question is how this educational need can be effectively met? A recent study suggests the importance of a unified messaging strategy from all providers interacting with the patient [ 31 ]. However, a messaging strategy without actual messaging tools is unlikely to be successful.…”
Section: The Path Forwardmentioning
confidence: 99%